Motorfietsbedryf: Geleenthede vir markontwikkeling - D. Lessing (South African Journal of Business Management, 1987)
– Motor-cycle industry: Opportunities for market development The South African motor-cycle industry has experienced a constant decline in sales since 1981, that is, a drop from 84 000 units sold during 1981 to a sales figure of 24 509 units for 1985. This decline in sales poses a threat to the profitability and survival of the motor-cycle industry in South Africa. Up to this point in time the marketing efforts of the motor-cycle industry were mainly directed towards the white consumer market. In order to bring about an upturn in motor-cycle sales, this study looked into the feasibility of a marketing effort by the motor-cycle industry aimed at the black consumer market. The findings of the study revealed that blacks currently view motor-cycles as a dangerous means of transport, used mainly by high speeding dare-devils. However, by the compilation of an optimum marketing strategy, the motor-cycle industry should be able to overcome the above-mentioned objection of blacks against motor-cycles. The marketing mix strategy should reveal the following characteristics: (i) A marketing communication strategy which centres on the re-education of blacks, so that they perceive motor-cycles as an economical means of transport, requiring little parking space, instead of as 'heavy metal terrorists' with a horrifying accident record. (ii) A product offered to the black market which reveals its economical characteristics and, as preferred by blacks, is in the commuter class (200 cm3 - 500 cm3). (iii) A price that does not exceed R4000. (iv) The establishment of distribution outlets in white industrial areas with predominantly white sales personnel.
Keywords: 650